Influence of the metallic content on Pt-Ir/Nb 2 O 5 catalysts for decalin selective ring opening - Benitez, Viviana Monica (2017)
Ring opening of naphthenic rings on Pt-Ir catalysts supported on Nb2O5 was studied in this work. The catalysts were prepared by impregnation. In the case ofthe bimetallic catalyst,the total metallic load was kept constant while varying the individual quantity of impregnated Ir and Pt. The samples were characterized by transmission electron microscopy, X-ray diffraction, X-ray photoelectron spectroscopy, N2 sorption, NH3 TPD and model reactions (cyclohexane dehydrogenation and cyclopentane hydrogenolysis). The decalin ring opening capacity of the catalysts was evaluated. Monometallic Ir and Pt catalysts as well as bimetallic catalysts were active towards cyclohexane dehydrogenation and cyclopentane hydrogenolysis. Regarding the bimetallic catalysts, an increase on the Pt content promoted the cyclohexane dehydrogenationwhile hindering the hydrogenolytic activity. In the selective ring opening of decalin, the bimetallic catalysts presented activities comparable to the monometallic catalysts. Nonetheless, Ir(0.3%)/Nb2O5 catalyst presented the highest selectivity towards ring opening products with the lowest selectivity towards dehydrogenated products.